Development of a model for enhancing data security in medical information system - Bin-Ahmad, Habib (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Since many countries have started using Healthcare and Medical Emergency System, the data confidentiality becomes a major problem for healthcare and medical emergency system because it accumulates significant information. Sharing of private information via the Internet is easy to intercept by unauthorized parties. Attackers can access private information by capturing data transmission and forging themselves as authorized user. This research addresses the confidentiality issue by designing and developing a new model of data security in Medical Information System. It also provides a view of data sensitivity and suggested areas in cryptography to protect data at different sensitivity levels. Multilevel security in Medical Emergency System is proposed since a database contains information of various confidential levels of data. Information related Medical Emergency System is classified into several categories. A suitable cryptography is provided for each level of data sensitivity to support Medical Emergency System. The results of implementation indicated that it keeps specific sensitive data confidentially at a certain degree with a good performance even though we applied triple key encryption mechanism and multilevel security by comparing with SSL and PGP. Performance, response time, receiving and sending speed are the factor of test. Those tests were performed with a prototype of medical emergency system data in our research group case in Malaysia.